Development and validation of the leisure lifestyle and satisfaction assessment: A comprehensive tool for evaluating leisure engagement - En-Chi Chiu; Shu-Chun Lee (PLoS ONE, 2025)
Leisure activities play a pivotal role in enhancing the overall well-being and quality of life in people with schizophrenia. Leisure lifestyle and satisfaction provide important leisure-related information on how people with schizophrenia effectively engage in and benefit from leisure activities. The aim of the study was to develop a new measure with two sections (leisure lifestyle and leisure satisfaction): the leisure LIfestyle and SAtisfaction measure (LISA). Literature review, expert consultation, and cognitive interviews were conducted to develop and verify the content of the two sections. The leisure satisfaction section was examined for construct validity, Rasch reliability, and ceiling/floor effects. Eight experts reviewed the content, and 15 people with schizophrenia participated in a cognitive interview. Subsequently, 200 people with schizophrenia from one psychiatric center completed the two sections of the measure. The leisure lifestyle section comprised three items designed to assess personal values associated with engaging in leisure activities and preferences for leisure activities in the present and future. The leisure satisfaction section included 14 items to assess the level of satisfaction derived from engagement in leisure activities and demonstrated unidimensionality with infit and outfit mean squares ranging from 0.77 to 1.27 and 0.75 to 1.27, respectively, while the eigenvalue of the first contrast was 2.2. The leisure satisfaction section showed a sufficient Rasch reliability of 0.90 and no ceiling/floor effect (0.5–3.5%). The LISA can simultaneously assess leisure lifestyle and satisfaction, offering detailed insights into the leisure activities that people with schizophrenia are attracted to and their perceived enjoyment of these activities. The participants of this study were recruited from a single institution and we excluded people with schizophrenia with severe cognitive impairments, which may restrict generalizability. Future research is warranted to recruit people with schizophrenia from multiple institutions to cross-validate our findings.